The effect of corn starch and Kappa-Carrageenan probiotic encapsulation on growth and immune response in Chinook salmon (Oncorhynchus tshawytscha) - Maureen Frances Latimer; Manuel Soto-Dávila; Ivan Cadonic; Paul Craig; Brian Dixon (Comparative Immunology Reports)
Probiotics offer a promising alternative to antibiotics for managing aquaculture diseases, but their efficacy depends on maintaining stability during storage, feeding, and gastrointestinal transit. To achieve this, coating agents like corn starch and kappa-carrageenan are used in probiotic feed preparation, though some coatings may have unintended adverse effects. A feed trial was conducted to assess the impact of coating agents on growth and immune performance in Chinook salmon. Three treatments were tested: regular feed, regular feed coated with corn starch and k-carrageenan, and probiotic-supplemented feed with the same coating. The probiotic feed included a mixture of Pediococcus acidilactici MA18/5M and Limosilactobacillus reuteri LRE2. Fish growth was determined at 0-, 1-, 3-, 7-, 28, and 42-days post diet supplementation, and head kidney, spleen, and hindgut were collected. Transcripts encoding il-1b, il-8, and tgfb were evaluated by qPCR. Additionally, in the hindgut, cdh1, cldn15, jam1a, muc2, marveld2, vil1, and zo-1 were assessed to determine changes in gut barrier integrity. No significant differences in weight or length were observed between treatments measured over 42 days. The proinflammatory cytokines il-1b and il-8 in the spleen and head kidney showed no significant changes with the coating or probiotic treatments. However, the regulatory cytokine tgfb was significantly modulated. In the hindgut, all three transcripts and gut barrier integrity genes were modulated on day 1, day 7, or both in coated treatments. These findings indicate that corn starch and k-carrageenan as a combined coating agent has no short-term adverse effects on Chinook salmon growth or immunity and is effective for delivering probiotics to enhance fish health in aquaculture.